High speed uniaxial compression tests on ice - Sweeney, J. N.; Jones, S. J. (National Research Council of Canada. Institute for Marine Dynamics, 1994)
The Joint Research Project Arrangement #6 (JRPA 6) between Canada and FiNewfoundlandand required, amongst other things, that IMD conduct high speed uniaxial compression tests on ice in an effort to obtain the strength of ice at speeds typical of ice-propeller interaction. These speeds are estimated to be about 30ms-1. It was decided, therefore, to conduct uniaxial compression tests at speeds as high as possible with the available equipment, approximately 1 ms-1. While this was not as high as when impacted by a propeller, it was at least 10 times faster than any results in the literature. Results are given in this report for freshwater and "Baltic" sea ice. NRC publication: Yes